MENJAGA TRADISI KAMPUNG ADAT CIKONDANG DI TENGAH ARUS MODERNISASI - Faisa Khalidah; Alifia Hasya Nadhira, Elmalia Maulidina Tsani, Ghina Zahidatushalihah, Lusy Amelia Nasution, Mamat S (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
This research goals to verify in depth how the people of Cikondang Traditional Village in Lamajang Village, Pangalengan District, Bandung Regency, maintain ancestral traditions in the midst of a stronger trend of modernization. The main issue raised is the extent to which cultural values, customary laws, and traditional social structures are still able to survive and be implemented consistently in the midst of changes in lifestyles and global technology. Apply a descriptive case study method also a qualitative approach, which allows researchers to understand the meaning and cultural practice holistically. Data was obtained by participatory observation techniques, in-depth interviews, also documentation of traditional activities, with key sources such as traditional figures, traditional assistants, and the younger generation. The research results show that the Cikondang community is able to maintain the continuity of tradition through a non-coercive customary law system, a traditional deliberation mechanism, and value regeneration through the active involvement of youth in cultural activities. In addition, people also make limited adaptations to digital media as a means of traditional documentation, while maintaining the boundaries of traditional ethics. Tradition functions as a dynamic, spiritual, and contextual system of ethics and social law.